AKTUALISASI DAN HABITUASI NILAI-NILAI DASAR PNS PADA PERKULIAHAN PERSAMAAN DIFFERENSIAL - Jahring Jahring; Muhammad Hasan; Yuli Purbaningsih (Jurnal Karya Pendidikan Matematika, 2021)
This research aims to know the habituation of basic values of civil servants (accountability, nationalism, public ethics, quality commitment, and anti-corruption) toward increasing student learning outcomes at the differential equations coursework. This research is a pre-experimental study with the design of one group Pretest-posttest control design with students of 2016 mathematics education study programs of the Sembilanbelas November Kolaka University as samples amounting to 36 people. Data retrieval is conducted with a questionnaire on learning styles and student learning outcomes at the differential equation coursework. The actualization and habituation of the basic values of civil servants in students can improve character, positive habits, and student learning outcomes on differential equations. Inferentially indicated with a value of sig. = 0.000 < α = 0.05. So habituation of basic values of civil servants is significant in increasing the student learning outcomes at the differential equation coursework.